Evidence for Environmental Dissemination of Antibiotic Resistance Mediated by Wild Birds - Wu, Jiao; Huang, Ye; Rao, Dawei; Zhang, Yongkui; Yang, Kun (Frontiers in Microbiology, 2018)
ABSTRACT The aquatic bird, egret, could carry antibiotic resistance (AR) from a contaminated waterway (Jin River, Chengdu, China) into the surrounding environment (Wangjianglou Park). A systematic study was carried out on the unique environmental dissemination mode of antibiotic resistance (AR) mediated by birds. The minimum inhibitory concentrations (MICs) of various antibiotics against the environmental Escherichia coli isolates were used to evaluate the bacterial AR at the environmental locations where these isolates were recovered, i.e. the Jin River water, the egret feces, the park soil and the campus soil. The level of AR in the park soil was significantly higher than that in the campus soil that was seldom affected by the egrets, which suggested that the egrets mediated the transportation of AR from the polluted waterway to the park. Genotyping of the resistant E. coli isolates via repetitive-element PCR (rep-PCR) gave no strong correlation between the genotypes and the AR patterns of the bacteria. So, the transfer of resistant strains should be not the main mode of AR transportation in this process. The results of real-time PCR revealed that the abundance of antibiotic resistance genes (ARGs) and mobile genetic element (MGE) sequences (transposase and integrase genes) declined along the putative transportation route. The transportation of ARGs could be due to their linkage with MGE sequences, and horizontal gene transfer (HGT) should have contributed to the process. The movable colistin-resistance gene mcr-1 was detected among the colistin-resistant E. coli strains isolated from the river water and the egret feces, which indicated the possibility of the environmental dissemination of this gene. Birds, especially the migratory birds, for the role they played on the dissemination of environmental AR, should be considered when studying the ecology of AR.